Damage monitoring in composite structures via vibration based method: metal-composite bonded joints and sandwich structures - Flor, Felipe Rendeiro (2016)
The present document covers the studies over Structural Health Monitoring systems via vibration based methods. The topic is organized in two parallel studies. The first one analyzes the integrity of metal-composite single lap bonded joints. The second one approaches similar analyses for sandwich structures. The monitoring was made by investigating the dynamic response both computationally and experimentally to verify the reliability of applying vibration based SHM procedures, specifically with the objective of identifying the presence of debonding damage. The dynamic responses were obtained via accelerometers and piezoelectric sensors placed on top of the investigated structures (on the outward surface). The purpose for the accelerometers is to provide reference data for the analyses involving the piezoelectric sensors. Different metrics of damage identification were investigated, all working over a determined frequency range. They quantify the damage by analyzing either the magnitudes or phase angles of the dynamic responses among the undamaged and damage structures. This present work proposed modifications to some methodologies of damage quantification found in the literature and compared the results. The new metrics offered more reliable values for the damage quantification on several of the analyses. It was verified that the metrics are valid for the scenarios observed in the present study. The experimental analyses showed also the influence on the dynamic response due to the position of small elastomeric elements. In regards to the finite element analyses, the computational models showed similar results to the experimental data, the more accurate ones being the models for the bonded joints. For the computational models, improvements can be applied into the piezoelectric sensor (e.g. by using new finite element formulations), as well as the region of debonding (e.g. by using contact algorithms). It is important to highlight that the elastic properties of the skins for the sandwich structure were obtained by the literature, so the model can be improved in the future by applying properties obtained experimentally.